Multidisciplinary Approach in the Diagnosis and Treatment of Twin Anemia Polycythemia Sequence in Monochorionic Twin Pregnancies: Case Report - Fortún-Agud, Marina; Marfil-González, María; Monis-Rodríguez, Susana; Suarez-Arana, Maria; Blasco-Alonso, Marta; Jiménez-López, Jesús Salvador; Narbona-Arias, Isidro (MDPI, 2024)
Twin anemia–polycythemia sequence (TAPS) in monochorionic twin pregnancies is a potentially serious complication caused by unidirectional vascular anastomoses in the placenta, resulting in one anemic donor twin and one polycythemic recipient twin. Diagnosis of this condition is achieved through Doppler ultrasound assessment of the difference between the MoM of the peak systolic velocity of the middle cerebral artery between the twins, establishing the diagnosis with a delta value >0.5 MoM. Management of this situation is individualized and may include intrauterine transfusions, intrauterine laser treatment, and expectant management through ultrasound monitoring of both fetuses to prevent complications. In severe cases, pregnancy termination may be necessary. It is essential that these pregnancies are managed by a multidisciplinary team of professionals, including obstetricians specialized in fetal medicine and neonatologists, to ensure the best possible outcome for both the mother and the fetuses. Early detection and treatment are crucial in the management of pregnancies complicated by twin anemia–polycythemia sequence. The main objective of this article is to conduct a review of the existing literature on the anemia–polycythemia sequence in monochorionic pregnancies, emphasizing the exceptional nature of the presented case due to its spontaneous occurrence, which has a very low prevalence compared to post-laser TAPS cases. It also discusses the different treatment options, highlighting the importance of expectant management and individualization in each case.
Keywords: Embarazo - Complicaciones y secuelas; Anemia; TAPS; Monochorionic pregnancy; Intrauterine transfusion; MCA-PSV; Fetoscopic laser treatment; Expectant management